Publication of Notary Positions on Personal Social Media Accounts - Sani Satriangga Atmaja (Sultan Agung Notary Law Review, 2021)
A notary is a public official who is authorized to make an authentic deed with perfect evidentiary power. The position of a Notary is a Public Position that upholds the dignity and trust of the community so that in carrying out its duties, it must adhere to the prevailing laws and regulations and the Code of Professional Ethics. Based on the provisions of the Professional Code of Ethics, a Notary is prohibited from publishing his position or self-promotion, while in this digital era it is not uncommon for a Notary to list his position on his social media accounts. The purpose of this study is to explain and analyze the legal consequences of the publication of a notary position and how to apply sanctions and solutions for violations of the code of ethics according to Act No. 2 of 2014 concerning the position of notary and the code of ethics of a notary. The method used in this study is the normative juridical method, the specifications in this study are descriptive analytical, the data used are secondary data, using data collection sourced from library research that produces primary law materials, secondary law materials, and tertiary law materials, problems analyzed with the theory of Triadism Law and the theory of Legal Effectiveness. The results of this study indicate that the prohibition on the publication of Notary Positions for Notaries is based on the fact that a Notary as a position that provides services to the public requires the trust of the public, thus Notaries are obliged to uphold their nobility of dignity in accordance with the Law on Notary Positions and the Notary Code of Ethics. The legal consequences for a Notary who publish his Notary Position in Social Media accounts are not in accordance with the oath / promise of Position that has been uttered and mandated by the Notary Position Act, and violates the prohibition provisions in the Notary Code of Ethics.